Purchase Intention Analysis in Augmented Reality Marketing: SOR Implementation Framework - Christiarini, Renny; Rooney; Putra, Edy Yulianto (Yayasan Sinergi Kawula Muda, 2026)
The rapid competition in the developing industry makes it increasingly important for business actors and marketers to pay attention to several important factors that can determine consumer purchasing decisions, namely based on the SOR framework. The researcher intend to expand literature by extending the S-O-R framework to the context of AR-based marketing in the telecommunications sector, by introducing a novel conceptual model connecting augmentation, product informativeness, and personalized recommendations to purchase intention via choice beliefs and perceived usefulness. The research approach used is quantitative research, by distributing questionnaires to 308 telecommunications service users in Batam City. The findings reveal that augmentation and product informativeness have a significant effect on choice trust. Product informativeness also have a significant direct effect on purchase intentions, although personalized recommendations cannot prove a significant relationship with purchase intentions. Regarding its mediation effect, researchers proved that choice trust is able to mediate the relationship between augmentation and product informativeness with purchase intentions. Perceived usefulness is able to mediate the relationship between product informativeness and purchase intentions, personalized recommendations do not significantly influence purchase intentions. It is important for telecommunication service companies to boost purchase intentions by building trust in choice, benefits felt by customers by maximizing the usefulness of augmentation-related features, product informativeness, and ability to provide effective recommendations for customers. Future researchers can make efforts to implement further research related to augmented reality marketing factors in their influence on purchase intentions, with different variable or research object.